KAITAN IgE SPESIFIK METODE IMUNOBLOT TERHADAP ELISA PADA RINITIS ALERGI (Association Between Specific IgE Immunoblot Method with ELISA on Allergic Rhinitis) - Aryati Aryati; Dwi Retno Pawarti; Izzuki Muhashonah; Janti Tri Habsari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Allergic rhinitis is an allergic disease that is most often found beside bronchial asthma and eczema with the prevalence of is about33.3%, 9.8% and 11.2% respectively. The main examinations of allergic rhinitis are Skin Prick Test (SPT) and specific IgE, becausethe sensitivity and specificity of specific IgE examination depend on the examination method. To know the diagnostic value of specificIgE immunoblot examination by determination and were compared with ELISA in patients with allergic rhinitis. The cross-sectionaldesign of the study is con-ducted on patients at the Outpatient Clinic Department of ENT-Head and Neck from May until October 2014.Patients were grouped as diagnosis of allergic rhinitis and non-allergic non-infectious rhinitis based on clinical signs and symptoms,physical examina-tion, positive in SPT examination with or without an increase in total serum IgE and/or blood eosinophils. SpecificIgE immunoblot was conducted by using Foresight®, Acon Laboratories and the ELISA method using Allercoat™. The sensitivity andspecificity of inhalant allergen -specific IgE immunoblot Foresight® method was 73.9% and 42.9%, respectively. The sensitivity andspecificity of inhalant allergen -specific IgE ELISA method was 67.4% and 57.1%, respectively. The results of these two methods havea correlation coefficient 0.531 with p=0.000. The sensitivity and specificity of ingestan allergen specific IgE immunoblot Foresight®method was 41.3% and 85.7%, respectively. The sensitivity and specificity of ingestan allergen specific IgE ELISA method was 17.4 and78.6%, res-pectively. Results of these two methods have a correlation coefficient 0.375 with p=0.003. Based on this study of specificIgE immunoblot and ELISA methods, both have diagnostic sensitivity and specificity, which are almost the same. The sensitivity ofimmunoblot method inhalant allergens are superior to ELISA. The Immunoblot method ingestan allergen specificity is superior toELISA.